The Place of 'Higher Law' in the Quotidian Practice of Law: Herein of Practical Reason, Natural Law, Natural Rights, and Sex Toys - Brennan, Patrick McKinley (2010)
The question of the place of higher law in the ordinary practice of law is even now dogged by the brooding omnipresence caricature. This Article seeks to introduce and apply a philosophically defensible account of natural law, the one defended by Thomas Aquinas, to various problematics of contemporary law and jurisprudence. The Article argues that such higher law is not so high as to be relevant only to sexy constitutional questions, as is often supposed, but to everything we do in law. The Article argues that liberals and conservatives alike should acknowledge both the place of natural law in the positive law and the contingent/prudential limits on judges' authority to speak the natural law directly from the bench. Much of the Article is framed as a response to Steven Smith's Law's Quandary (Harvard 2004)